Comparing the Efficacy of Sequential and Standard Quadruple Therapy for Eradication of H. Pylori Infection - Razavizadeh, Mohsen; Arj, Abbas; Madani, Maryam; Gilassi, Hamidreza (Acta medica (Hradec Kralove), 2020)
BACKGROUND: The aim of this study was comparison the effectiveness of sequential and standard quadruple therapy on eradication of H. pylori infection. METHODS: This clinical trial study was conducted on 160 patients with dyspepsia or gastroduodenal ulcer. Patients were randomly divided into two groups. Group A (standard regimen) received omeprazole, amoxicillin, clarithromycin and bismuth subcitrate for 2 weeks. Group B (sequential regimen) received omeprazole and amoxicillin in 5 days and omeprazole, tinidazole and levofloxacin in 5 days. After the end of treatment regimens, 20 mg omeprazole was administered twice daily for 3 weeks. H. pylori eradication was assessed 2 months after antibiotic treatment via fecal antigen. RESULTS: Frequency of H. pylori eradication in group A and B was observed in 55 (68.8%) and 63 patients (78.8%), respectively. No significant difference was seen between two groups, regarding H. pylori eradication (p = 0.15). The most common side effects in group A, B were bitterness of mouth (63.8%) and nausea (16.2%), respectively (p H. pylori infection, higher rate of H. pylori eradication was seen in group B than group A. Thus, sequential regimen was a more appropriate regimen with fewer complications.
Keywords: klarithromycin; standard triple-drug therapy; Humans; Omeprazole; lidé středního věku; tinidazol; Female; Aged; dospělí; levofloxacin; Clarithromycin; senioři; lidé; Organometallic Compounds; amoxicilin; organokovové sloučeniny; Tinidazole; Adult; eradication; ženské pohlaví; Helicobacter Infections; Helicobacter pylori; Male; Middle Aged; Levofloxacin; H. pylori infection; Sequential therapy; Amoxicillin; mužské pohlaví; kombinovaná farmakoterapie; omeprazol; infekce vyvolané Helicobacter pylori; Drug Therapy, Combination